Intercostal Administration of Liposomal Bupivacaine as a Prognostic Nerve Block Prior to Phenol Neurolysis for Intractable Chest Wall Pain. (1st March 2014) - Yin, Chen; Matchett, Gerald
ABSTRACT Inadequate pain relief from systemic medications is common in patients with advanced malignancy. Chest wall pain secondary to tumor involvement of chest wall structures can be challenging to manage with systemic medications, and occasionally patients benefit from interventional procedures such as intercostal nerve blocks and neurolysis. In this report, the authors describe the case of a 58-year-old woman with advanced non-small cell lung cancer with tumor invasion into the third thoracic rib. After reaching maximum tolerated doses of transdermal fentanyl, oral hydromorphone, and oral ketamine, the patient elected for intercostal nerve blockade and neurolysis. Prognostic nerve blockade was performed using liposomal bupivacaine administered via intercostal approach. This formulation of bupivacaine provided an excellent prognostic blockade, which lasted for approximately 96 hours. This extended period of time allowed the patient to fully evaluate the prognostic blockade, prior to proceeding with neurolysis with phenol. This case suggests that liposomal bupivacaine may be a valuable adjunctive agent for prognostic blockade prior to neurolysis for cancer pain.